PENGARUH STRATEGI SPONSORSHIP PT.GOJEK INDONESIA DI LIGA 1 INDONESIA TERHADAP KEPUTUSAN PEMESANAN GO-JEK DI KOTA PALEMBANG - Herman, Herman; Naruliza, Esty (Fakultas Ekonomi Universitas IBA, 2018)
PT. Gojek Indonesia (GO-JEK) was a firm engaged in the business of transportation based on application smart phone. GO-JEK do strategy sponsorship by become one of the main sponsors in the implementation of a football gojek traveloka liga1 indonesia. With strategy sponsorship, how does it influence on reservations go-jek in palembang ?Sponsorship is the financial support from an organization, person, or activity in exchange for publicity and brand association.The purpose of this research is to know how the influence of sponsorship strategy PT.Gojek Indonesia in league 1 Indonesia of the decision of reserving go-jek Palembang. The data used in this research was the primary data obtained from the data the questionnaire. Method of withdrawal of samples on this research using Cluster Sampling.The results of this research indicate that is no significant influence against decisions ordering GO-JEK in Palembang. Testing is done based on the regression results table that indicates that the value tcalculate > ttable (1,332 > 1.65).the conclusion, the decision ordering GO-JEK in Palembang is affected by the sponsorship of 0.7%. While the rest of 99.3% are other factors that are not included in this study such as quality of service, prices, methods of payment and the variety of products offered.